Intro to Redux - Dennison, Justin (Packt Publishing, 2024)
In this course, you will embark on a journey to master Redux, the powerful state management library for JavaScript applications. Starting with an overview, you will get acquainted with the core concepts and structure of Redux, setting a solid foundation for your learning. The subsequent video will delve into the reasons why Redux is essential, providing a clear understanding of its significance in modern web development. As you progress, you will explore the fundamental principles that underpin Redux. These principles are crucial for effectively implementing and utilizing Redux in your projects. Additionally, the course addresses the unique challenges of managing lists within Redux, offering strategies and best practices to handle these scenarios effectively. The course concludes with a comprehensive wrap-up, reinforcing the knowledge gained and ensuring you are ready to apply Redux with confidence. Designed for developers with a basic understanding of JavaScript, this course is perfect for those looking to enhance their state management skills. By the end of the course, you will have a thorough understanding of Redux, its core principles, and how to manage state efficiently in your applications.
Online resource; title from title details screen (O'Reilly, viewed June 17, 2024)
Keywords: Java (Computer program language); Web site development; Web sites -- Design; Application software -- Development; Internet programming; Java (Langage de programmation); Sites Web; Développement; Sites Web; Conception; Logiciels d'application; Développement; Programmation Internet; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet